Cohort profile: the Men and Parenting Pathways (MAPP) Study: a longitudinal Australian cohort study of men's mental health and well-being at the normative age for first-time fatherhood. Issue 7 (27th July 2021) - Macdonald, Jacqui A; Francis, Lauren M; Skouteris, Helen; Youssef, George J; Graeme, Liam G; Williams, Joanne; Fletcher, Richard J; Knight, Tess; Milgrom, Jeannette; Di Manno, Laura; Olsson, Craig A; Greenwood, Christopher J
Abstract : Purpose: The Men and Parenting Pathways (MAPP) Study is a prospective investigation of men's mental health and well-being across the normative age for transitioning to fatherhood. This includes trajectories and outcomes for men who do and do not become fathers across five annual waves of the study. Participants: Australian resident, English-speaking men aged 28–32 years at baseline were eligible. Recruitment was over a 2-year period (2015–2017) via social and traditional media and through engagement with study partners. Eight hundred and eighteen eligible men consented to participate. Of these, 664 men completed the first online survey of whom 608 consented to ongoing participation. Of the ongoing sample, 83% have participated in at least two of the first three annual online surveys. Findings to date: Three waves of data collection are complete. The first longitudinal analysis of MAPP data, published in 2020, identified five profiles that characterise men's patterns of depressive symptom severity and presentations of anger. Profiles indicating pronounced anger and depressive symptoms were associated with fathers' lack of perceived social support, and problems with coparenting and bonding with infants. In a second study, MAPP data were combined with three other Australian cohorts in a meta-analysis of associations between fathers' self-reported sleep problems up to 3 years postpartum and symptoms of depression, anxiety and stress. Adjusted meta-analytic associations between paternal sleep and mental health risk ranged from 0.25 to 0.37. Future plans: MAPP is an ongoing cohort study. Waves 4 and 5 data will be ready for analyses at the end of 2021. Future investigations will include crossed-lagged and trajectory analyses that assess inter-relatedness and changing social networks, mental health, work and family life. A nested study of COVID-19 pandemic-related mental health and coping will add two further waves of data collection in a subsample of MAPP participants.